1991
DOI: 10.1177/016235329101500108
|View full text |Cite
|
Sign up to set email alerts
|

What Became of the Kids Who Participated in the 1981 Johnson Early College Summer Arts Program?

Abstract: Results are reported of a follow-up study conducted nine years after a group of twenty-seven adolescents, judged talented in the visual and performing arts, participated in the Johnson State Early College Summer Arts Program. In this research, which utilized a questionnaire, the Self-Directed Learning Readiness Scale, and telephone interviews, information was provided about members of this population, now young adults. It was revealed that: 1) art still plays an important role in their lives; 2) they possess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…From the outset of the period of development of the LAP, these four constructs were referred to in order of the precursors (desire) first and persistence last. Having no logical or scientific reasons to place resourcefulness and initiative in any particular order, the DRIP order was employed because it provided a handy acronym (Confessore, 1991). Later, a path‐analytic study conducted by Ponton et al (2003) set the desire construct as the starting point and determined that the strongest probability of order was indeed DRIP.…”
Section: Discussionmentioning
confidence: 99%
“…From the outset of the period of development of the LAP, these four constructs were referred to in order of the precursors (desire) first and persistence last. Having no logical or scientific reasons to place resourcefulness and initiative in any particular order, the DRIP order was employed because it provided a handy acronym (Confessore, 1991). Later, a path‐analytic study conducted by Ponton et al (2003) set the desire construct as the starting point and determined that the strongest probability of order was indeed DRIP.…”
Section: Discussionmentioning
confidence: 99%
“…Early and advanced opportunities in the arts play a vital role in the later development of professional artists. It has been found that talented students who participate in programming for the visual arts report long-term affective and career gains (Confessore, 1991). These programs should be learner-centered (Burton, 2000) and emphasize the production of artwork (Burton, 1994).…”
Section: Importance Of Arts Instructionmentioning
confidence: 99%
“…They might give up, attempt to conform, or channel their talents to destructive and antisocial behaviors. Studies indicate that talented students-except those who are permitted to proceed according to their own rates and consistent with their own goals-often feel lonely and bored, and sometimes withdraw from school (Confessore 1991;Landau 1990). Dayton and Feldhusen (1989) found that high motivation/persistence and intellectual/academic ability are common traits of the talented.…”
Section: Characnrlstlcs Of Talennd Learnersmentioning
confidence: 99%
“…The participation of talented students in vocational programs plays an important role in career choice (Confessore 1991;Phelps 1988).Talented learners are encouraged to enroll in vocational education programs and academic courses for enrichment. Enrichment experiences help talented students explore, identify, and utilize their talents.…”
Section: Technical Education For Talented Studentsmentioning
confidence: 99%
See 1 more Smart Citation